Efeitos de uma intervenção terapêutica pelo exercício físico e orientação em saúde em indivíduos obesos - Rezende, Adriana D' Aprile (2008)
Obesity presents itself as a worldwide epidemic and it is one of the most important factors for the development of cardiovascular and metabolic problems. Individuals who are overweight and obese, that means the ones with Body Mass Index (BMI) ≥ 25 kg / m2, in both genders, are predisposed to cardiovascular diseases especially when associated with an abdominal circumference of risk. The increase in abdominal fat is one of the most serious cardiovascular, insulin resistance, hypertension and dyslipidemia risk factors amongst others. The dyslipidemias are mainly represented by high levels in fractions of LDL-cholesterol and low levels of HDL-cholesterol. The water activities seem to be a good method of physical intervention for obese individuals as a result of the physical properties of water, which can improve physical fitness and help to control or treat biochemical changes related to total cholesterol, fractions of cholesterol and triglycerides. This study is characterized as experimental and aimed to check the influence of an aquatic physical protocol, associated or not to nutritional guidelines, on lipid metabolism (total cholesterol, fractions of cholesterol and triglycerides) and the functional capacity of obese individuals. There was a selection of 16 individuals of both sexes aged between 45 and 77 years who were divided into 2 groups: Group Exercise / Nutrition (GEN) and Group Exercise without Nutrition (GEWN). The aquatic race in shallow pool was the chosen modality which was performed for 12 weeks at a frequency of 3 times per week. There were improvements in the physical fitness, total cholesterol and LDL-cholesterol in both groups. There were no significant differences in the values of HDL-cholesterol, triglycerides and VLDL-cholesterol in any of the groups. Words-keys: water exercises; obesity; physical fitness; lipemic profile.